The Colostomy of Duret for the High Risk Patient. Issue 3 (16th March 2021) - DiGiacomo, Jody C.; Lehman, Mark
Abstract: Background : Heitzer and Duret described the surgical creation of colostomy in the 1700s, more than a century before the introduction of anesthesia. With the ever increasing degree of frailty in patients of advanced age who require surgical intervention, a simplified methodology for the creation of a colostomy based on their original reports is described and the advantages for use in high risk patients and the critical care setting is discussed. Methods : Eleven patients underwent simplified colostomy under local anesthesia, without complication. Results : All colostomies functioned normally within hours. There were no bleeding or infectious complications, nor peri-operative adverse events. Conclusions : Colostomy formation can be safely performed under local anesthesia when the patient is considered too high risk to undergo general anesthesia.